Early Childhood Teachers' Attitudes Toward Gender-Neutral Pedagogical Practices: Insights from Indonesia and Pakistan - Muhammad Rehan Sabir; Dewi Candraningrum (Journal of Early Childhood Education Perspectives, 2026)
This exploratory cross-sectional, cross-national study examined early childhood teachers' attitudes toward gender-neutral pedagogical practices in Indonesia and Pakistan. Structured interviews were conducted with 80 teachers (40 per country) working with children aged 3–6 years. Participants were recruited through purposive sampling from urban early childhood education centers. Attitudes toward gender-neutral pedagogical practices were operationalized across four dimensions: gender-inclusive language, mixed-gender participation, non-stereotyped learning materials, and balanced behavioral expectations. Data were analyzed using descriptive statistics, independent-samples t-tests, and multiple regression analyses. Indonesian teachers reported higher attitude scores across all dimensions, with moderate to very large effect sizes (Cohen’s d = 0.45–1.10). Educational attainment (β = .28) and participation in professional development (β = .31) were positively associated with teachers’ attitudes. The model explained 42% of the variance in attitudes (R² = .42, adjusted R² = .39). The findings indicate that higher formal qualifications and participation in professional development are associated with more favorable attitudes toward non-stereotyped classroom practices within the sampled early childhood settings.